Photoacoustic imaging of breast microcalcifications: a preliminary study with 8-gauge core-biopsied breast specimens. - Ga Ram Kim (Public Library of Science (PLoS), 2014)
Background We presented the photoacoustic imaging (PAI) tool and to evaluate whether microcalcifications in breast tissue can be detected on photoacoustic (PA) images. Methods We collected 21 cores containing microcalcifications (n = 11, microcalcification group) and none (n = 10, control group) in stereotactic or ultrasound (US) guided 8-gauge vacuum-assisted biopsies. Photoacoustic (PA) images were acquired through ex vivo experiments by transmitting laser pulses with two different wavelengths (700 nm and 800 nm). The presence of microcalcifications in PA images were blindly assessed by two radiologists and compared with specimen mammography. A ratio of the signal amplitude occurring at 700 nm to that occurring at 800 nm was calculated for each PA focus and was called the PAI ratio. Results Based on the change of PA signal amplitude between 700 nm and 800 nm, 10 out of 11 specimens containing microcalcifications and 8 out of 10 specimens without calcifications were correctly identified on blind review; the sensitivity, specificity, accuracy, positive predictive and negative predictive values of our blind review were 90.91%, 80.0%, 85.71%, 83.33% and 88.89%. The PAI ratio in the microcalcification group was significantly higher than that in the control group (the median PAI ratio, 2.46 versus 1.11, respectively, P =  .001). On subgroup analysis in the microcalcification group, neither malignant diagnosis nor the number or size of calcification-foci was proven to contribute to PAI ratios. Conclusion Breast microcalcifications generated distinguishable PA signals unlike breast tissue without calcifications. So, PAI, a non-ionizing and non-invasive hybrid imaging technique, can be an alternative in overcoming the limitations of conventional US imaging.